(untitled) (Research, Society and Development, 2026)
Historically, the occupation of the Amazon was driven by exploratory cycles and large industrial infrastructure projects that favored disordered urbanization, especially in floodplain areas. Originally marked by a symbiosis with nature and incipient infrastructure, Abaetetuba-PA underwent a profound socio-spatial restructuring, where the industrial advent reconfigured the local landscape and radically transformed the relationships between society and the Amazonian territory. This study aims to understand the relationship between the construction of the Albras and Alunorte (Hydro) industrial unit in Barcarena in the 1980s and the process of disordered urbanization in the São Sebastião neighborhood in the city of Abaetetuba-PA, addressing the reflections of this industrialization on environmental injustice. The procedures adopted for this research employ an interdisciplinary approach, of a descriptive and exploratory nature, based on qualitative research. The collection of secondary data is based on the bibliographic analysis of books and scientific articles relevant to the topic. The results demonstrate that industrialization in Abaetetuba-PA, driven by the Albras/Alunorte complex, has reconfigured the territory through intense migratory flows and disordered urban growth. This process has generated fragmented occupation, where the coexistence of industrial plants and peripheral neighborhoods—such as São Sebastião—evidences a profound socio-spatial segregation. It is concluded, therefore, that future industrial projects must be subject to rigorous impact studies and urban management that rejects the relaxation of regulations, aiming for socially just and environmentally balanced development.